Effects of serum albumin on the photophysical characteristics of synthetic and endogenous protoporphyrin IX - D.C.K. Codognato; F.S. Pena; E.R. dos Reis; A.P. Ramos; I.E. Borissevitch (Brazilian Journal of Medical and Biological Research, 2022)
The study of the interaction of synthetic protoporphyrin IX (PpIXs) and protoporphyrin IX extracted from Harderian glands of ssp Rattus novergicus albinus rats (PpIXe) with bovine serum albumin (BSA) was conducted in water at pH 7.3 and pH 4.5 by optical absorption and fluorescence spectroscopies. PpIXs is present as H- and J-aggregates in equilibrium with themselves and with monomers. The PpIXs charge is 2− at pH 7.3 and 1− at pH 4.5. This increases its aggregation at pH 4.5 and shifts the equilibrium in favor of J-aggregates. In spite of electrostatic attraction at pH 4.5, where BSA is positive, the binding constant (Kb) of PpIXs to BSA is 20% less than that at pH 7.3, where BSA is negative. This occurs because higher aggregation of PpIXs at pH 4.5 reduces the observed Kb value. At both pHs, water-soluble PpIXe exists in the monomeric form with the charge of 1− and its Kb exceeds that of PpIXs. At pH 4.5, its Kb is 12 times higher than that at pH 7.3 due to electrostatic attraction between the positively charged BSA and the negatively charged PpIXe. The higher probability of PpIXe binding to BSA makes PpIXe more promising as a fluorescence probe for fluorescence diagnostics and as a photosensitizer for photodynamic therapy. The existence of PpIXe in the monomeric form can explain its faster cell internalization. Aggregation reduces quantum yields and lifetimes of the PpIXs excited states, which explains higher phototoxicity of PpIXe toward malignant cells compared with PpIXs.